Acceptor substitution engineering of BODIPY-based organic photosensitizers with aggregation-induced emission for organelle localization and photodynamic anticancer therapy - Chaojie Shen; Mintao Xie; Liying Pan; Binbin Wu; Wenxuan Zhang; Yuying Yuan; Yuan Chen; Yun-Yun Quan; Xiaoxia Ye; Zu-Sheng Huang (Materials & Design, 2023)
Photodynamic therapy (PDT) is a promising noninvasive treatment for cancer. Researchers have focused on improving the therapeutic effects of PDT in recent years. Subcellular organelles are the building blocks of cells, and their destruction can lead to cell dysfunction or even death. Photosensitizers (PSs) with precise organelle targeting capacity can not only kill cancer cells effectively but also help reduce PS dose, minimize side effects, and avoid drug resistance. Herein, four homologous luminogens with aggregation-induced emission (AIE) characteristics through acceptor substitution engineering are designed and synthesized to specifically anchor to mitochondria, cell membrane and lysosome through slight structural tweaks, and reactive oxygen species (ROS) are efficiently produced under light irradiation, which significantly enhance the therapy efficacy of PDT. Notably, biological studies have shown that membrane-targeted PS, TBVP exhibits more powerful therapeutic effects than other three PSs (TBPy, TBPy-Bu and TBPy-TA) at the same concentration. The highly effective anti-tumor activity of TBVP was evaluated successfully in vitro and in vivo. In addition, TBVP can promote cell autophagy to induce cell death. We thus believe the anchoring organelles approach described here represents an attractive therapeutic approach in photodynamic therapy.